The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1987
DOI: 10.1038/bjc.1986.226
|View full text |Cite
|
Sign up to set email alerts
|

Black tea consumption and cancer risk: A prospective study

Abstract: (RR=4.2). This positive association (P=0.0007) could not be accounted for by age or alcohol intake. We also observed a weaker but significant negative association of black tea intake and prostate cancer incidence (P=0.020). There were no significant associations between black tea consumption and cancer at any other site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(51 citation statements)
references
References 25 publications
1
50
0
Order By: Relevance
“…Epidemiological studies, although not conclusive, have suggested the protective role of green tea against CaP development (10)(11)(12)(13)(14). Recent laboratory studies have indicated that green tea and its polyphenolic constituents impart inhibitory effects on the activities of many enzymatic, metabolic, and signaling pathways that have relevance to cancer development and progression (31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies, although not conclusive, have suggested the protective role of green tea against CaP development (10)(11)(12)(13)(14). Recent laboratory studies have indicated that green tea and its polyphenolic constituents impart inhibitory effects on the activities of many enzymatic, metabolic, and signaling pathways that have relevance to cancer development and progression (31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies, although inconclusive, suggest a protective effect of tea consumption on some cancer types in humans (11,12). Limited epidemiological studies indicate that people who consume tea regularly may have a lower risk of CaP (13,14). Further, the Japanese and Chinese populations who regularly consume tea, especially green tea, have one of the lowest incidences of CaP in the world (15,16).…”
mentioning
confidence: 99%
“…Epidemiological studies, though not conclusive, have suggested the protective role of green tea against CaP development (10)(11)(12)(13)(14). Recent laboratory studies have indicated that green tea and its polyphenolic constituents impart inhibitory effects on the activities of many enzymatic, metabolic and signaling pathways that have relevance to cancer development and progression (31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Since prostate cancer is typically diagnosed in men aged 50 years and older, even a slight delay in the onset and subsequent progression of the disease through the use of chemopreventive agent(s) could have important health benefits (2)(3)(4)(5) Epidemiological studies, though inconclusive, have suggested the protective role of green tea against prostate cancer development (6,7). Recent laboratory studies have indicated that green tea and its polyphenolic constituents impart inhibitory effects on the activities of many enrymatic, metabolic and signaling pathways that have relevance to cancer development and progression (8)(9)(10)(11)(12)(13). A number of studies have shown the growth inhibitory effects of green tea against many animal tumor bioassay systems including lung, skin and forestomach (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation